If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 = -1b + 6 Reorder the terms: 17 = 6 + -1b Solving 17 = 6 + -1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add 'b' to each side of the equation. 17 + b = 6 + -1b + b Combine like terms: -1b + b = 0 17 + b = 6 + 0 17 + b = 6 Add '-17' to each side of the equation. 17 + -17 + b = 6 + -17 Combine like terms: 17 + -17 = 0 0 + b = 6 + -17 b = 6 + -17 Combine like terms: 6 + -17 = -11 b = -11 Simplifying b = -11
| 8(2l+1)= | | 6a-10=4a+2 | | 2(2w-6)+2(w)=3(w+8) | | 4(a-3)= | | 9+3x=8x+12 | | X(90)=1050+375 | | (u+4)*10= | | 95.30=19.95+0.55x | | -5x-2(4-2x)=2+7 | | 15+.20m=25.00+.10m | | x+8+16=0 | | (q-5)*2= | | -5-2(4-2x)=2+7 | | 2x+44=x-12 | | 2(w-6)+2(w)=3(w+8) | | (e+5)*4= | | 0.5(2n+6)=0.2(8n-10) | | Y+-12=11 | | 5.95+0.06m=30 | | 4+11y-1=9y+21-7y | | 8(X-4)=350 | | 42-4X=200 | | 1-x=.4 | | 1.5(x+8)=5.7+0.6x | | 5x+113=11x-7 | | 2x-(5x+2)=9x-26 | | 3y-5=-8(6+5t) | | 11(t-3)+3t=7(2t+4)-10 | | 4x-7=-2x-19 | | 8.99(85)=650+x | | 6+25x=20x+8 | | 8(x-5)-6x=-26 |